EFFECT OF POLYVINYL PYRROLIDONE (PVP) ON IN VITRO MATURATION AND CLEAVAGE RATE OF CAPRINE OOCYTES - AGARWAL, SIRBHI; SHARMA, JUHI R; KHARCHE, S D; GOEL, A K; JINDAL, S K (The Indian Journal of Animal Reproduction, 2023)
The exact role of action of serum and BSA in culture medium for oocyte maturation is still unknown. The replacement of these proteins with synthetic macromolecules such as polyvinyl pyrrolidone (PVP) need to be evaluated and compared with protein supplement in maturation medium. Therefore the present study was undertaken with two objectives vizTo study the effect of PVP on in vitro maturation of caprine oocytes and to evaluate the cleavage rate of oocytes matured in a medium supplemented with PVP. A total of 612 healthy cumulus oocyte complexes (COCs) were collected from 390 goat ovaries through puncture technique and were subjected to the following maturation treatments. Group-1: Maturation medium TCM-199 supplemented with 10% FBS, 3mg/ml BSA, LH (1 O ±g/ml), FSH (5 ±g/ml), L-glutamine (100 ±g/ml), sodium pyruvate (0.25 mM) and gentamycin (50±g/ml) and Group-2: Maturation medium TCM-199 supplemented with 3mg/ml PVP, LH (10 ±g/ml), FSH (5 ±g/ml), L-glutamine (100 ±g/ml), sodium pyruvate (0.25 mM) and gentamycin (50±g/ml)for 27 hr in humidified atmosphere of 5% CO2 at 38.501°C in CO2 incubator.In vitro maturation rate was assessed on the basis of cumulus expansion. Expanded oocytes were denuded by treating with 0.1 % hyaluronidase and used for further in vitro fertilization. Matured oocytes and 2-5 millions sperm/ml were co-incubated in 50 ±I drop ofFertilization medium (TALP medium+ 8 mg/ml) fatty acid free BSA and 100 ±g/ml heparin) for 18 hr. Fertilized oocytes of both groups were cultured in embryo development medium comprising of potassium simplex optimized Medium + 10 % FBS+ 3 mg/ml BSA) for cleavage and further embryo development.The Maturation and cleavage rate in group 1 and group 2 were 89.6% and 60.2% and 35.67% and 14.34%, respectively. Statistical analysis revealed that maturation rate and cleavage rate in maturation medium supplemented with serum is significantly higher as compared to PVP supplemented medium.